The Effectiveness Of Islamic Boarding Schools In Forming Children's Character - Besari, Anam (STAI MA'ARIF MAGETAN, INDONESIA, 2022)
Islamic boarding schools is one of the oldest educational institutions, it can even be said that Islamic boarding schools are one of the forerunners of education in Indonesia. Its existence is also very familiar in the midst of Indonesian society, not only among Muslims but in general almost all people are familiar with Islamic boarding schools. The role of Islamic boarding schools is very important in human development in the nation and state, especially in terms of maintaining the unity and integrity of this beloved republic of Indonesia. In the implementation of education, Islamic boarding schools prioritize education with good and noble character, both humans and their God, humans and others, even having character with their nation and state. In islamic boarding schools, the students will be prepared and trained in their attitude and character as soon as possible as a perfect Muslim. They will become tough individuals, so that in the future the students can be accepted and even very likely to be examples of figures in the midst of society for their attitudes and character.